Elevating Employee Performance: The Role of Extrinsic Motivation and Skill in a Bandung Hospital - Nuraisah, Risma; Kadir, Kadir; Komara, Anton Tirta; Nurdiansyah, Haris; Satria, Rd Okky (P3M, STIE Pasundan, Bandung, Indonesia., 2024)
This study seeks to investigate the effects of extrinsic motivation and competence on staff performance and their combined influence in a hospital in Bandung. The employed research method is both descriptive and verificative. The study population comprises staff at a hospital in Bandung, with a sample size of 55 respondents determined using Slovin's algorithm. Data collection was executed via questionnaires, and data analysis was carried out using route analysis with the aid of SPSS 17 for Windows. Statistical analysis revealed that extrinsic motivation exerts a direct influence of 17.7%, an indirect effect via competence of 11.8%, and a cumulative effect of 29.5%. The competence variable exerts a direct influence of 31.2%, an indirect effect via extrinsic motivation of 11.8%, and a cumulative effect of 43%. The coefficient of determination (R²), represented as a percentage, signifies that the combined influence of all independent variables—extrinsic drive and competence—on the performance variable is 0.726 or 72.6%. Additionally, additional unexamined elements affecting performance are indicated by the value ɛ = 0.274 or 27.4%. Consequently, it may be inferred that extrinsic incentives and competence substantially influence staff performance at a hospital in Bandung. This research indicates that hospital management should prioritize boosting extrinsic motivation and cultivating employee competencies to elevate overall performance. The hospital may cultivate a more productive work atmosphere by employing tactics that promote motivation, such as recognition programs and professional development opportunities, resulting in improved patient care outcomes.